Evaluation of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in chronic plaque psoriasis - Sudeshna Mondal; Samudra Guha; Abanti Saha; Loknath Ghoshal; Debabrata Bandyopadhyay (Wolters Kluwer Medknow Publications, 2022)
Background: Psoriasis is a common inflammatory dermatological condition and affects 2-3% population worldwide. Psoriasis area and severity index (PASI) and body surface area (BSA) are two commonly used scales used to measure disease severity in psoriasis patients. However, these scales are plagued by weaknesses as inter-observer variation and insufficient evaluation of micro-vascular inflammation. Thus, it is necessary to have an objective and simple measure of the severity of inflammation. The ratio of neutrophils-to-lymphocytes (NLR) and platelets-to-lymphocytes (PLR) are simple and inexpensive markers of systemic inflammatory response that can be measured as part of a complete blood count and are already used in the setting of inflammatory diseases. The utility of the NLR and PLR in psoriasis however, remains relatively unexplored. Aims and Objectives: The present study was undertaken to assess if NLR, PLR and C-reactive protein were altered in chronic plaque psoriasis patients as compared to controls and also to determine correlation of NLR and PLR values with disease severity as measured by PASI. Methods: This case control study consisted of equal numbers (45 each) chronic plaque psoriasis patients and control subjects. The subjects were evaluated by way of history taking, clinical and blood examination. Thereafter, the results were tabulated and examined statistically. Results: Our study results indicate that psoriasis patients tended to have a higher neutrophil count, lymphocyte count, NLR and C-reactive protein in comparison the control subjects (P < 0.05). Conclusion: We concluded that such easily available and low cost indices of systemic inflammation are raised in psoriasis patients and are positively correlated with the severity of involvement. They can thus not only be used to monitor the effect of systemic drugs in psoriasis.